The Caucasus : an introduction - De Waal, Thomas (Oxford University Press, 2018)
The Caucasus is an updated version of an essential guide that has introduced thousands of readers to a complex and fascinating region. Thomas de Waal gives a brief and stimulating portrait of Armenia, Azerbaijan, Georgia, their multi-layered history, seemingly intractable conflicts and complex politics.